Investor behavior in evaluating portfolio performance: do investor behave rationally? - Puspitaningtyas, Zarah (Institute of Computer Science (IOCS), 2025)
Financial theory assumes that investors are rational individuals. However, several empirical studies show that investors tend to act contrary to financial theory and cannot be explained in models based on investor rationality. How does investor behavior in making investment decisions relate to evaluating portfolio performance? This study applies mixed methods to prove portfolio performance evaluation through optimal portfolio formation and reveals its usefulness in making investment decisions. This study uses a single index model approach to evaluate portfolio performance and a structured interview method. The study sample is companies listed on the IDXHIDIV20 Index for the 2021 to 2023 period and investment manager as informants. These results prove that stock prices fluctuate in the same direction as the market index and each security has a different level of return and risk. Even though investors evaluate portfolio performance, excessive optimism, as a psychological factor, tends to control investor behavior in the investment decision making process. The research results support the behavioral financial theory that investors tend to act irrationally, because the decisions taken are not completely based on rational considerations but are also influenced by various kinds of biases that have an impact on investors' actions. However, investors' actions are seen as something normal. The results of the study contribute to the financial field to drive the efficiency of resource allocation and provide signals that reflect the value of the company